Exocrine Pancreas in Cats With Diabetes Mellitus. (January 2016) - Zini, E.; Ferro, S.; Lunardi, F.; Zanetti, R.; Heller, R. S.; Coppola, L. M.; Guscetti, F.; Osto, M.; Lutz, T. A.; Cavicchioli, L.; Reusch, C. E.
Pancreatitis has been described in cats with diabetes mellitus, although the number of studies currently available is very limited. In addition, ketoacidosis has been hypothesized to be associated with pancreatitis in diabetic cats. The aims of the present study were to investigate whether diabetic cats have pancreatitis and to determine if pancreatitis is more frequent with ketoacidosis. Samples of pancreas were collected postmortem from 37 diabetic cats, including 15 with ketoacidosis, and 20 control cats matched for age, sex, breed, and body weight. Sections were stained with hematoxylin and eosin, double-labeled for insulin/CD3, insulin/CD20, insulin/myeloperoxidase, insulin/PCNA, and glucagon/Ki67, and single-labeled for Iba1. A previously proposed semiquantitative score was used to characterize pancreatitis, along with counts of inflammatory cells. Scores of pancreatitis and the number of neutrophils, macrophages, and lymphocytes in the exocrine pancreas did not differ between diabetic and control cats or between diabetic cats with and without ketoacidosis. Of note, PCNA-positive acinar cells were increased ( P = .002) in diabetic cats, particularly near islets ( P < .001). Ki67-positive acinar cells were increased only near islets ( P = .038). Ketoacidosis was not linked to proliferation. The results suggest that histopathologic evidence of pancreatitis may not be more frequent in diabetic cats and that ketoacidosis may not be associated with it at the time of death. Augmented PCNA-positive acinar cells might indicate increased proliferation due to chronic pancreatitis. The reason behind the prevalent proliferation of acinar cells surrounding pancreatic islets deserves further investigation.